Investigation of swift heavy I-ion irradiation effects on damage in silicon dioxide thin film - S. Intarasiri (2018)
Silicon dioxide (SiO < inf > 2 < /inf > ) is a next-generation dielectric material for semiconductor processing. In particular, a thin film of amorphous-SiO < inf > 2 < /inf > (a-SiO < inf > 2 < /inf > ) on silicon wafers has many technological applications in microelectronics. However, a-SiO < inf > 2 < /inf > /Si structures can be severely degraded in the presence of radiation, due to the formation of defects in SiO < inf > 2 < /inf > and its interface. In this study, we investigated the irradiation-induced defects of SiO < inf > 2 < /inf > by swift I-ions. Thermally a-SiO < inf > 2 < /inf > film was grown on Si wafer and subsequently irradiated with swift I-ions at energies of 10, 20 and 30 MeV at low or high fluences and at room or high temperatures. The effects of the irradiation were investigated following the changing of the infrared transmittance properties of the samples. From the measurements, we concluded that the energy, fluence and substrate temperature during irradiation greatly affected defects in the film. The electronic energy loss mechanism of the tens-MeV I-ion irradiation of a-SiO < inf > 2 < /inf > /Si structure plays a major role in the structure destruction.